Development and validation of a novel nomogram for predicting recurrent atrial fibrillation after cryoballoon ablation - Wei, Yue; Lin, Changjian; Xie, Yun; Bao, Yangyang; Luo, Qingzhi; Zhang, Ning; Wu, Liqun (Frontiers in Cardiovascular Medicine, 2023)
Background: Few studies have explored the use of machine learning models to predict the recurrence of atrial fibrillation (AF) in patients who have undergone cryoballoon ablation (CBA).We aimed to explore the risk factors for the recurrence of AF after CBA in order to construct a nomogram that could predict this risk. Methods: Data of 498 patients who had undergone CBA at Ruijin Hospital, Shanghai Jiaotong University School of Medicine, were retrospectively collected. Factors such as clinical characteristics and biophysical parameters during the CBA procedure were collected for the selection of variables. Scores for all the biophysical factors-such as time to pulmonary vein isolation (TTI) and balloon temperature-were calculated to enable construction of the model, which was then calibrated and compared with the risk scores. Results: A 36-month follow-up showed that 177 (35.5%) of the 489 patients experienced AF recurrence. The left atrial volume, TTI, nadir cryoballoon temperature, and number of unsuccessful freezes were related to the recurrence of AF (P <.05). The area under the curve (AUC) of the nomogram's time-dependent receiver operating characteristic curve was 77.6%, 71.6%, and 71.0%, respectively, for the 1-, 2-, and 3-year prediction of recurrence in the training cohort and 77.4%, 74.7%, and 68.7%, respectively, for the same characteristics in the validation cohort. Calibration and data on the nomogram's clinical effectiveness showed it to be accurate for the prediction of recurrence in both the training and validation cohorts as compared with established risk scores. Conclusion: Biophysical parameters such as TTI and cryoballoon temperature have a great impact on AF recurrence. The predictive accuracy for recurrence of our nomogram was superior to that of conventional risk scores.